The Popularity and Intensity of Engineering Undergraduate Out‐of‐Class Activities. Issue 4 (6th December 2018) - Simmons, Denise R.; Van Mullekom, Jennifer; Ohland, Matthew W.
Abstract: Background: Although researchers have documented the outcomes of various out‐of‐class activities for undergraduate students, less attention has been given to student perspectives on activity category and activity levels, particularly when considering demographics such as gender and race/ethnicity. Purpose/Hypothesis: This study aims to create a more nuanced profile of engineering undergraduate engagement in out‐of‐class activities disaggregated by gender, race/ethnicity, and level of activity. As an exploratory study, its goal is to identify patterns that can be explored in the future. Design/Method: A purposive sample of 649 engineering students from three institutions provided complete survey responses that were quantitatively analyzed using frequency tables, diverging bar charts, and calculated odds ratios. This study included an intentional focus on gender and racial/ethnic differences. Results: Job and Sports were most commonly identified as the top out‐of‐class activity for engineering students. Select pre‐professional activities and activities related to the humanities, arts, environment, and civic life were identified less frequently as top activities. Significant differences in choice of top activity and level of activity were found when comparing students by gender and race/ethnicity. Conclusion: A better understanding of engineering student engagement in out‐of‐class activities helps guide actions of program administrators and educators and the direction of future research exploring out‐of‐class engagement. Such opportunities can be shaped to improve engagement, particularly among underrepresented groups.